1991
DOI: 10.1007/bf02897690
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Lead and Cadmium by Maize Seedlings and the Effect of Heavy Metals on the Activity of Phosphoenolpyruvate Carboxylase Isolated from Maize

Abstract: Maize seeds and five-day-old maize seedlings were incubated in media containing Pb 2+ at concentrations of 50, 100, and 200 mg 1 -l and Cd 2+ at concentrations of 1, 5, 10 and 50 mg 1 -l. After five days of incubation, both heavy metals were determined by means of AAS following wet mineralisation of roots and shoots. The results obtained indicate that Pb 2 § were transported to shoots from roots at a lower rate than Cd 2+.Phosphoenolpyruvate carboxylase (PEPC) isolated from germinating maize seeds was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…There is some reports that excess concentrations or hyper accumulation of some heavy metals in soils such as Cd(II), Cr(VI), CuII), Ni(II), and Zn(II) have caused the disturbanceof both natural aquatic and terrestrial ecosystems (GardeaTorresdey et al, 1996;Meagher, 2000).tolerate high concentration of heavy metals and other toxic substances (Banuelos et al, 1997;Blaylock & Huang, 2000;Raskin & Ensley, 2000;Dahmani Muller et al, 2000). More over different studies have been conducted in order to evaluate the effects of different heavy metal concentrations on herbal organisms (Thompson et al, 1997;Raskin & Ensley, 2000) but in contrast there are small number of studies on seeds which have been exposed to the pollutants (Claire et al, 1991;Vojtechova & Leblova, 1991;Xiong, 1998). Judia and Fulekar (2008) reported that inhibitory effect of heavy metal on seed gerniantion sis concentration depedent process in alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…There is some reports that excess concentrations or hyper accumulation of some heavy metals in soils such as Cd(II), Cr(VI), CuII), Ni(II), and Zn(II) have caused the disturbanceof both natural aquatic and terrestrial ecosystems (GardeaTorresdey et al, 1996;Meagher, 2000).tolerate high concentration of heavy metals and other toxic substances (Banuelos et al, 1997;Blaylock & Huang, 2000;Raskin & Ensley, 2000;Dahmani Muller et al, 2000). More over different studies have been conducted in order to evaluate the effects of different heavy metal concentrations on herbal organisms (Thompson et al, 1997;Raskin & Ensley, 2000) but in contrast there are small number of studies on seeds which have been exposed to the pollutants (Claire et al, 1991;Vojtechova & Leblova, 1991;Xiong, 1998). Judia and Fulekar (2008) reported that inhibitory effect of heavy metal on seed gerniantion sis concentration depedent process in alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals persist indefinitely in soil thereby posing an ever-increasing threat to human health and agriculture (Leyval et al 1995). Metal toxicity primarily depends on plant species as they exhibit considerable genetic variation in their ability in tolerating amounts and the concentration of specific heavy metals (Vojtechova and Leblova 1991). Some heavy metals are essential micronutrients for plants but their excess may result in metabolic disorders and growth inhibition in most of the plant species (Claire et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Plants are known to have at least two defense mechanisms whereby they are able to incorporate metals into their tissues and continue to survive. In response to the toxic elements, plants can synthesize metalchelating proteins called metallothioneins [15]- [17]. Another mechanism which may account for the accumulation of heavy metals in plants is the synthesis of phytochelatins, as suggested by Rauser [18].…”
Section: Resultsmentioning
confidence: 99%